Diagnosis of cardiac tamponade with transesophageal echocardiography following the induction of anesthesia for suspected testicular torsion - Stephen M McHugh (Annals of Cardiac Anaesthesia, 2015)
Transesophageal echocardiography (TEE) is a valuable tool for evaluating hemodynamic instability in patients under general anesthesia. We present the case of a 28-year-old man who presented with complaints of testicular pain concerning for testicular torsion. After induction of general anesthesia for scrotal exploration and possible orchiopexy, the patient developed severe and persistent hypotension. Using intraoperative TEE, the diagnosis of pericardial tamponade was made, and an emergent pericardial window was performed.